2020
DOI: 10.1152/jn.00468.2019
|View full text |Cite
|
Sign up to set email alerts
|

Right frontal eye field has perceptual and oculomotor functions during optokinetic stimulation and nystagmus

Abstract: The right frontal eye field (rFEF) is associated with visual perception and eye movements. rFEF is activated during optokinetic nystagmus (OKN), a reflex that moves the eye in response to visual motion (optokinetic stimulation, OKS). It remains unclear whether rFEF plays causal perceptual and/or oculomotor roles during OKS and OKN. To test this, participants viewed a leftward-moving visual scene of vertical bars and judged whether a flashed dot was moving. Single pulses of transcranial magnetic stimulation (TM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 114 publications
(161 reference statements)
0
11
0
Order By: Relevance
“…The right hemisphere -in right handers, as in the present study-specializes in vestibular processing, which allows an individual to orient themselves in space based on visual and proprioceptive cues (e.g., body posture and orientation; Mast et al, 2014;Besnard et al, 2015;Dieterich and Brandt, 2015). Within this context, the right frontal eye field (implicated in the present study) has been uniquely identified as important to visuospatial perception (Mastropasqua et al, 2020). Collectively, the preference for right-hemisphere activation in these brain areas suggest an increased emphasis on regulating visuomotor expressions, likely facilitated by repeated deployment of reactive control mechanisms in response to spontaneously evolving situations on stage.…”
Section: Bx Reaction Timementioning
confidence: 49%
See 1 more Smart Citation
“…The right hemisphere -in right handers, as in the present study-specializes in vestibular processing, which allows an individual to orient themselves in space based on visual and proprioceptive cues (e.g., body posture and orientation; Mast et al, 2014;Besnard et al, 2015;Dieterich and Brandt, 2015). Within this context, the right frontal eye field (implicated in the present study) has been uniquely identified as important to visuospatial perception (Mastropasqua et al, 2020). Collectively, the preference for right-hemisphere activation in these brain areas suggest an increased emphasis on regulating visuomotor expressions, likely facilitated by repeated deployment of reactive control mechanisms in response to spontaneously evolving situations on stage.…”
Section: Bx Reaction Timementioning
confidence: 49%
“…Both BA6 and BA8 have been directly implicated in reactive control processes (Brass et al, 2005;Forstmann et al, 2008;Braver et al, 2009). Both areas have also been associated with orchestrating complex visuomotor interactions (Mastropasqua et al, 2020), which are characteristic of the reactive control aspect of active experiencing. Integrating these viewpoints together, it is likely that BA6 and BA8 facilitate deployment of reactive control.…”
Section: Bx Reaction Timementioning
confidence: 99%
“…One candidate would be the dorsal attentional network, key parts of which are activated during OKN, such as the frontal eye fields (FEF; Ruehl et al, 2019). In a recent TMS study, disrupting the FEF during OKN slowed the eye movement (Mastropasqua et al, 2020). Here we can apply the same logic in the opposite direction: if intensive hand gripping facilitated the dorsal attentional network, this could account for the speeding of slow phase velocity of OKN.…”
Section: Discussionmentioning
confidence: 99%
“…Future event-related studies relying on time-frequency analysis (but forfeiting frequency precision for greater time precision) will be necessary to investigate the time-course of the inhibitory effects produced over the visual cortex after each handgrip, or those over the motor cortex during OKS. A recent study reported that frontal eye field TMS during OKS modulated the anterior-posterior alpha EEG balance, the OKN slow phase velocity, and simultaneous perceptual processing, interestingly with no effects of TMS over primary motor cortex (Mastropasqua et al 2020). It would also be important to determine which other cortical and subcortical areas are modulated after each handgrip, which may contribute to the currently observed acceleration of the slow-phase velocity of OKN.…”
Section: Discussionmentioning
confidence: 99%
“…Combined transcranial magnetic stimulation and electroencephalography and an optokinetic-stimulation motion-discrimination task revealed multiple related yet dissociable roles within the FEF, which included perceptual processing during optokinetic simulation, generation of OKN, and maintenance of alpha oscillations. 74 …”
Section: Triggered Nystagmusmentioning
confidence: 99%